Macroscopic analysis of time dependent plasticity in Ti alloys. (10th October 2022) - Xiong, Yi; Karamched, Phani S.; Nguyen, Chi-Toan; Collins, David M.; Magazzeni, Christopher M.; Tarleton, Edmund; Wilkinson, Angus J.
Highlights: Numerical method for stress relaxation curve analysis. Key parameters for time dependent plasticity as a function of temperature. Strain rate sensitivity analysis. Dwell fatigue effect is more significant by oxygen alloying but is suppressed by the addition of molybdenum. Graphical abstract: Abstract: Component failure due to cold dwell fatigue of titanium and its alloys is a long-standing problem which has significant safety and economic implications to the aviation industry. This can be addressed by understanding the governing mechanisms of time dependent plasticity behaviour of Ti at low temperatures. Here, stress relaxation tests were performed at four different temperatures on three major alloy systems: commercially pure titanium (two alloys with different oxygen content), Ti-6Al-4V (two microstructures with differing β phase fractions) and Ti-6Al-2Sn-4Zr- x Mo (two alloys with different Mo content x = 2 or 6, and portion of β phase). Key parameters controlling the time dependent plasticity were determined as a function of temperature. Both activation volume and energy were found to increase with temperature in all six alloys. It was found that the dwell fatigue effect is more significant by oxygen alloying but is suppressed by the addition of Mo. The presence of the β phase did not strongly affect the dwell fatigue, however, it was suppressed at high temperature due to the low strain rate and strain rate sensitivity.